PENGARUH METODE CERAMAH DAN DIALOG TERHADAP MOTIVASI BELAJAR - Diny Kristianty W (MADINASIKA, 2021)
This research is motivated by the low motivation of students to learn, this is thought to be due to the use of unsuitable learning methods. The low level of absorption of students towards Islamic religious subjects is evidenced by the results. This is the main problem, because learning motivation will be related to student learning outcomes in Islamic education subjects. The research method used in this research is analytic, to determine the level of the relationship between one variable and another. To obtain the necessary data, as part of the analytic regression design, researchers used quantitative methods by distributing questionnaires. To support the data collected through questionnaires, observations and interviews were also carried out with related parties, namely teachers and school principals. The results of this study prove that the application of the lecture method in Islamic Education learning is carried out well. The application of the dialogue method in Islamic Education learning is well implemented. The learning motivation of students of SD Negeri Balongan 1, Indramayu Regency is perceived as sufficient. There is a positive and significant effect of the application of the lecture method on learning motivation. There is a positive and significant effect of the application of the dialogue method on learning motivation. The positive and significant effect of the simultaneous application of the lecture method and the dialogue method on learning motivation.